Selection of institute for public higher education (IPTA) among first-year students using Fuzzy AHP / Muhammad Afiq Salihin Jafar ... [et al.] - Jafar, Muhammad Afiq Salihin; Md Dom, Nor Lela; Zakaria, Nur Raudhatul Hidayah; Tarmudi, Zamali; Saudah@Suhadak, Nurulzulaiha (Universiti Teknologi MARA, Negeri Sembilan, 2023)
There are 20 IPTAs, or institutes for public higher education, in Malaysia. Institut Pengajian Tinggi Awam is referred to as IPTA in Malay. All students, whether Malaysian or international, are provided with tuition at the Institute for Public Higher Education. Each category of institution has a distinct specialty, such as research universities, comprehensive universities, or focused universities. In addition, there are some IPTAs just for Bumiputera students only (Khairul Azran Hussin, 2019). The students who wish to register in the Institute for Public Higher Education struggle to decide which IPTA is ideal for them because there are so many different groups of institutions. Then, to overcome this issue, we will use the Fuzzy Analytic Hierarchy Process (FAHP) technique. The Fuzzy Analytic Hierarchy Process (FAHP) is a fuzzy logic-based Analytic Hierarchy Process (AHP) (Santoso et al., 2016). The FAHP approach is comparable to the AHP method.